2012
DOI: 10.1136/bcr-2012-006476
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal rupture and optic nerve injury with equipment designated as ‘child-safe’

Abstract: SummaryBlunt ocular trauma from a child's plastic foam-covered toy baseball bat caused traumatic optic neuropathy and choroidal rupture in a 9-year-old child. The examination revealed a visual acuity of 6/60, a relative afferent pupillary defect, optic nerve swelling, commotio retinae and retinal haemorrhages. There was no orbital fracture or intraorbital haematoma on CT scanning. Optical coherence tomography showed macular oedema and disruption of the retinal pigment epithelium and Bruch's membrane. The child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…23,24 In such cases, choroidal rupture can be an accompanying feature. 25 Because of the severity of optic nerve and, often, intraocular damage that is usually associated with direct injury to the anterior optic nerve, the prognosis for anterior TON usually is poor in this setting, regardless of treatment. 26 The prognosis for anterior TON caused by indirect injury, however, is not as clear.…”
Section: Location Of Injurymentioning
confidence: 99%
“…23,24 In such cases, choroidal rupture can be an accompanying feature. 25 Because of the severity of optic nerve and, often, intraocular damage that is usually associated with direct injury to the anterior optic nerve, the prognosis for anterior TON usually is poor in this setting, regardless of treatment. 26 The prognosis for anterior TON caused by indirect injury, however, is not as clear.…”
Section: Location Of Injurymentioning
confidence: 99%
“…[14][15][16][17] Other reported injuries include assault, 4,9,11,18 or trauma from a stone, 10,11,19,20 brick, 11 ice ball, 18 champagne cork, 4 elastic cord, 21 or other miscellaneous objects. 9,22,23 Choroidal rupture has been reported after a kick by a horse, 18 as well as after deployment of a car airbag. 24 They have been reported in neonates from forceps used during delivery.…”
Section: Causesmentioning
confidence: 98%
“…Anterior TON, either direct or indirect, causes swelling of the optical disc with other signs of optic neuropathy. As a result, it may lead to retinal ischemia, anterior ischemic optic neuropathy, central retinal vein occlusion, choroidal rupture, or a composite of this situation [ 37 ].…”
Section: Optic Nerve Injury Classificationmentioning
confidence: 99%
“…Mesenchymal stem cells derived from human umbilical cords (hUC-MSCs) have been investigated to treat some diseases, such as spinal cord injury, Parkinson’s disease, and cornea-related diseases [ 37 , 108 ]. A rat study has shown that intravitreal injection of human periodontal ligament-derived stem cells (PDLSCs) may improve RGC survival after optic nerve injury [ 109 ].…”
Section: Experimental Treatmentsmentioning
confidence: 99%